The complete molecular sequence of chloroplast genome of Lablab purpureus (L.) Sweet. Issue 3 (4th March 2021) - Li, Na; Bai, Ji-Qing; Gao, Su; Yang, Lei; Li, Jing; Du, Shao-Bing; Wang, Xiao-Ping
Abstract: The complete molecular sequence of chloroplast genome of Lablab purpureus (L.) Sweet was firstly assembled and characterized using Illumina sequencing technology. It is 151916 bp in length, with a GC content of 35.4%, and has a typical quadrant structure, including a large single-copy region (LSC), a pair of inverted repeat regions (IRs) and a small single-copy region (SSC), the sequence length is 81132, 53244, 17540 bp, respectively. There are 131 genes in the L. purpureus chloroplast genome, including 84 encoding protein genes, 8 rRNA genes, and 38 tRNA genes. Phylogenetic analysis showed that L. purpureus clustered into a large evolutionary clade with three Vigna species.